Embedded 3D printing of multi-layer, self-oscillating vocal fold models. (24th May 2021) - Greenwood, Taylor E.; Thomson, Scott L.
Abstract: The biomechanics of human voice production are commonly studied using benchtop silicone vocal fold models that mimic the vibration of their in vivo counterparts. These models often have multiple layers of differing stiffness that represent human vocal fold tissue layers and are fabricated using a multi-step casting process. The purpose of the present study is to introduce and demonstrate a process for fabricating functional multi-layer vocal fold models using an alternative approach, termed embedded 3D printing, that is a hybrid of casting and 3D printing. In this paper the fabrication process is described. Analysis of the resulting geometric and stiffness characteristics of the layers, including layer elastic modulus values ranging from less than 1 kPa to approximately 40 kPa, is presented. The results of tests demonstrating that the models are capable of sustained phonomimetic vibration are given. Capabilities and limitations of the embedded 3D printing process are discussed. It is concluded that the process has the potential to contribute to voice biomechanics research by facilitating prospective improvements in the fabrication, design, and functionality of multi-layer vocal fold models.